The System of Regional Taxation: Legal and Economic Analysis - I. V. Lipatova (Учёт. Анализ. Аудит)
The regional taxation plays a major role in the formation of budget income part of the sub-federal units of the Russian Federation. The federal structure of the state always causes the need to deal with the main problem of any federation: the separation or delegation of the powers of the federal center and the territorial subjects. One of the parts of the general problem of the division of powers between the federal and regional levels of government is the definition and the determination of the tax jurisdiction. Due to the fact that Russia is a federal state with a high differentiation of her regions by the quantity and the quality of the capital or production resources, where it is necessary to keep balance while solving two main problems: to preserve the unity of the economic space of the country and to promote the regional development, taking into account the specifics of the sub-federal entities - the problem of the taxation powers scale of the authorities at various levels is one of the priorities for the tax policy. The most important of the regional taxes (as its own source of budget incomes of the economic subjects of the Russian Federation) is the property tax imposed on organizations. The article examines the whole range of issues covering the legislative consolidation of authoritarian powers of the entities of the Russian Federation. First of all, there were considered the constitutional provisions regarding the regulation of the legal forms of control related to the approval and the introduction of tax framework of reference of the Russian Federation and its subjects. There were also issues analyzed regarding how the general constitutional principles of the distribution of the tax competence are implemented in the federal legislation, especially in the Tax Code of the Russian Federation describing the property tax of the organizations. One can fairly state that once the sub-federal units of the Russian Federation are granted the authority to control and monitor all the elements regarding the regional taxation basing on the example of the property tax of the organizations, the sub-federal units of the Russian Federation will be secured with the constitutional rights and the real chances to conduct their own taxation policies. The purpose of this research is to study the scope, content and the limits of authority of the sub-federal units of the Russian Federation in terms of the legal regulation of regional taxes on the example of the property tax of the organizations.